2022
DOI: 10.1002/cbic.202200138
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Productivity in Single‐Tile‐Based DNA Polyhedra Assembly by Simple Cation Replacement

Abstract: Cations such as divalent magnesium ion (Mg 2 + ) play an essential role in DNA self-assembly. However, the strong electrostatic shielding effect of Mg 2 + would be disadvantageous in some situations that require relatively weak interactions to allow a highly reversible error-correcting mechanism in the process of assembly. Herein, by substituting the conventional divalent Mg 2 + with monovalent sodium ion (Na + ), we have achieved one-pot high-yield assembly of tile-based DNA polyhedra at micromolar concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In this study, we have presented new results on DNA nanostructure self‐assembly in the presence of different monovalent and divalent cations. Our study complements existing studies on magnesium‐free assembly of DNA nanostructures (that only use Na + ) [ 31,43 ] and provides assembly conditions in a wider variety of cations. For the smaller DX motif, the structure has previously been assembled in 125 m m Ca 2+ to template morphology changes in calcium carbonate, [ 55 ] while here we show that the structure can be assembled in 10 m m Ca 2+ .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, we have presented new results on DNA nanostructure self‐assembly in the presence of different monovalent and divalent cations. Our study complements existing studies on magnesium‐free assembly of DNA nanostructures (that only use Na + ) [ 31,43 ] and provides assembly conditions in a wider variety of cations. For the smaller DX motif, the structure has previously been assembled in 125 m m Ca 2+ to template morphology changes in calcium carbonate, [ 55 ] while here we show that the structure can be assembled in 10 m m Ca 2+ .…”
Section: Discussionmentioning
confidence: 63%
“…A recent study that was published during our work showed that similar DNA tetrahedra can be assembled at higher Na + (100–600 m m ) and K + (400 m m ) concentrations. [ 43 ] To our knowledge, our study is the first to show assembly of a variety of DNA nanostructures in Ba 2+ , with assembly yields comparable to a Mg 2+ ‐containing buffer for the DX and the three‐point‐star motif as well as for the larger DNA origami triangle. While our work shows that a variety of DNA nanostructures can be assembled in different cations, the choice of cation would be dependent on the specific design of the structure and the application.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation